‘Joining the Academic Life’: South African students who succeed at University despite not meeting standard entry requirements - Vincent, Louise; Idahosa, Grace Eseosa (South African Journal of Higher Education, 2018)
At present the Swedish points system is one of the main determinants of an applicant either being refused or being granted entry into many South African universities. Using a grounded theory approach this paper interprets the experiences of participants whose school performance and therefore university ‘entry points’ were lower than the expected norm but who nevertheless succeeded at university, completing their degrees in the minimum time available and going on to higher degrees. The journeys of these participants – from low entry points to academic success -- suggests that points based on school performance are not necessarily the best way of identifying a student’s potential to succeed in the contemporary South African educational context. If their entry points were not a good indication of their ability to thrive at university, the article asks, what was it about these participants that accounts for their success? And what implications does this have for our practice not only with regard to admissions policies but also in relation to our responsibilities to students once they are admitted to higher education institutions?